2019
DOI: 10.1136/bmjopen-2018-025433
|View full text |Cite
|
Sign up to set email alerts
|

Doctors don’t Do-little: a national cross-sectional study of workplace well-being of hospital doctors in Ireland

Abstract: ObjectivesTo measure levels of occupational stress, burn-out, work–life balance, presenteeism, work ability (balance between work and personal resources) and desire to practise in trainee and consultant hospital doctors in Ireland.DesignNational cross-sectional study of randomised sample of hospital doctors. Participants provided sociodemographic data (age, sex), work grade (consultant, higher/basic specialist trainee), specialty, work hours and completed workplace well-being questionnaires (Effort–Reward Imba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 46 publications
(81 reference statements)
3
40
1
2
Order By: Relevance
“…Other studies highlighted the same factors as main sources of physicians' stress. 7,25,30,31 The combination of high perceived stress, and rather infrequent thoughts of leaving the profession aligns with Hayes et al's results: hospital doctors in Ireland complained of poor work-life balance and high work stress, but were nevertheless motivated to pursue their profession. 30 Other recent studies 13,14 also show that young physicians are highly motivated to practise as GPs.…”
Section: Comparison With Existing Literaturesupporting
confidence: 73%
See 1 more Smart Citation
“…Other studies highlighted the same factors as main sources of physicians' stress. 7,25,30,31 The combination of high perceived stress, and rather infrequent thoughts of leaving the profession aligns with Hayes et al's results: hospital doctors in Ireland complained of poor work-life balance and high work stress, but were nevertheless motivated to pursue their profession. 30 Other recent studies 13,14 also show that young physicians are highly motivated to practise as GPs.…”
Section: Comparison With Existing Literaturesupporting
confidence: 73%
“…These results align with findings from other studies that identified the training period as the phase most characterised by distress and difficulty. 4,29,30 Despite high stress levels, GPs had the highest mental wellbeing among the subgroups, and higher compared with the GP sample surveyed in the cross-sectional study of Murray et al (50.2 versus 54.2 in the present sample). These results show that after completion of the training period, wellbeing increases among practising Swiss GPs and is higher compared with a similar GP sample in the UK.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 62%
“…In fact, at the Social Summit for Fair Employment and Growth held in Gothenburg in November 2017, the WLB was proclaimed as a European pillar of social rights [12]. Despite this, the peculiarities of the work environment that surrounds the nursing profession makes it difficult to reconcile work and family life, preventing a high level of work satisfaction from being achieved [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the quantitative survey findings 23 and also with previous research internationally 19 and in Ireland—where only one in five hospital doctors surveyed were satisfied with their work–life balance. 24 This article illustrates the distress caused by work–life imbalance and its impact on male and female respondents. Although the work–life balance debate often focuses on the experiences of mothers of young children, our results highlight that work–life imbalance is a problem for both men and women and those with any caring responsibilities.…”
Section: Discussionmentioning
confidence: 99%